Penentuan Obat Penyakit Gigi pada Sistem Pendukung Keputusan Menggunakan Metode Topsis - Sari, Ika Yusnita; Sihombing, Marjones H.H; Rahmi, Elvika; Khairunnisa, Khairunnisa; Daeli, Cosmas Samuel (Cattleya Darmaya Fortuna, 2023)
The use of information technology is very helpful, especially decision making in determining dental disease drugs. When determining the drug for the buyer there are often errors in the determination of the drug. The criteria of the drug include the benefits of the drug, the dosage of the drug, the effect of the drug, the price and guarantee of the drug. There are many criteria in determining dental disease drugs, so the TOPSIS method is needed. This method is one of the decision-making methods where the chosen alternative is the best alternative that has the closest distance from the positive ideal solution and farthest from the negative ideal solution. From testing 8 types of drugs and 5 criteria. Of the 8 types of drugs, the type of M8 drug based on the largest preference value of 0.811 is the best dental disease drug.